Association between clinical factors and orofacial dyskinesias in anti‐N‐methyl‐D‐aspartate receptor encephalitis. Issue 7 (27th May 2022) - Hang, Hailun; Lin, Liuyu; Li, Danhui; Li, Jin; Shi, Jingping; Lu, Jie
Abstract: Background and Purpose: We aimed to determine whether demographic information, clinical characteristics, laboratory tests, and imaging features are associated with orofacial dyskinesias (OFLD) in patients with anti‐N‐methyl‐D‐aspartate receptor (NMDAR) encephalitis. Methods: In this retrospective study, patients who were diagnosed with anti‐NMDAR encephalitis were enrolled. All patients' factors, including demographic information, clinical characteristics, laboratory tests, and imaging features, were obtained at the time of hospitalization. The neurological function was assessed using the modified Rankin scale (mRS). Univariate and multivariate logistic regressions were used to examine the associations between clinical factors and OFLD. Results: In total, 119 patients (median age: 28.0 [19.0–41.0] years; 67 females) were recruited. Of 119 patients, 44 (37.0%) had OFLD. OFLD was associated with increased mRS at admission, serum sodium, lumbar puncture pressure, female biologic sex, fever, psychiatric symptoms, seizures, impaired consciousness, autonomic dysfunction, and central hypoventilation in univariate logistic regression, respectively. Multivariate regression analysis revealed that female biologic sex (odds ratios [OR], 4.73; 95% confidence interval [CI], 1.27–17.64; p = .021), increased mRS at admission (OR, 2.09; 95% CI, 1.18–3.71; p = .011), psychiatric symptoms (OR, 7.27; 95% CI, 1.20–43.91; p = .031), and seizures (OR, 5.11; 95% CI, 1.22–21.43; p = .026) were associated with OFLD, after adjusting for confounding factors. Conclusions: Our analysis suggests that the following clinical factors are associated with OFLD: female biologic sex, increased mRS at admission, psychiatric symptoms, and seizures. Abstract : Our analysis suggests that the following clinical factors are associated with OFLD: female biologic sex, increased mRS at admission, psychiatric symptoms, and seizures.